Rurbanisation of Traditional Authority Land: The Views of Villagers on Chiefs Granting Newcomers the Right to Occupy Land in Mokhurumela and Dikgale (Limpopo Province) - Molele, Mmatlou Annett (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.